PENERAPAN CARD-BASED GAME DAN KEAKTIFAN MAHASISWA PADA MATA KULIAH KONSEP DASAR MATEMATIKA TOPIK PEMECAHAN MASALAH - Mila Handiyani; Sintya Widhiacarni Atmanastusti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Mathematics learning in higher education requires strategies that can enhance students’ engagement in understanding concepts and solving mathematical problems. However, learning practices that remain predominantly lecturer-centered often result in suboptimal student participation. One alternative strategy is the use of a card-based game as an active learning approach. This study aimed to describe the implementation of a card-based game and student engagement in the Basic Mathematics Concepts course on the topic of mathematical problem-solving. The study employed a descriptive qualitative approach involving 30 students from the Elementary School Teacher Education (PGSD) program at IAHN Tampung Penyang Palangka Raya. Data were collected through observations, questionnaires, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the card-based game enhanced students’ cognitive, social, and affective engagement. Students became more active in discussions, expressing opinions, collaborating with peers, and developing strategies to solve mathematical problems. The novelty of this study lies in the use of a card-based game in a higher education Basic Mathematics Concepts course to simultaneously promote student engagement and mathematical problem-solving skills. The findings provide practical contributions for lecturers in designing more participatory learning environments and support students in developing critical thinking and collaborative skills. Therefore, the card-based game can serve as an alternative active learning strategy to support mathematics learning in higher education. ABSTRAK Pembelajaran matematika di perguruan tinggi memerlukan strategi yang mampu meningkatkan keterlibatan mahasiswa dalam memahami konsep dan menyelesaikan masalah matematis. Namun, pembelajaran yang masih cenderung berpusat pada dosen sering menyebabkan partisipasi mahasiswa kurang optimal. Salah satu alternatif yang dapat digunakan adalah card-based game sebagai bentuk pembelajaran aktif. Penelitian ini bertujuan mendeskripsikan penerapan card-based game serta keaktifan mahasiswa pada mata kuliah Konsep Dasar Matematika dengan topik pemecahan masalah matematis. Penelitian menggunakan pendekatan deskriptif kualitatif dengan subjek 30 mahasiswa PGSD di IAHN Tampung Penyang Palangka Raya. Data dikumpulkan melalui observasi, kuesioner, dan dokumentasi, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa card-based game meningkatkan keterlibatan mahasiswa secara kognitif, sosial, dan afektif. Mahasiswa menjadi lebih aktif berdiskusi, mengemukakan pendapat, bekerja sama, dan menyusun strategi penyelesaian masalah matematis. Kebaruan penelitian ini terletak pada pemanfaatan card-based game dalam pembelajaran Konsep Dasar Matematika di perguruan tinggi untuk mendorong keaktifan dan kemampuan pemecahan masalah secara bersamaan. Temuan penelitian memberikan kontribusi bagi dosen dalam merancang pembelajaran yang lebih partisipatif serta membantu mahasiswa mengembangkan kemampuan berpikir kritis dan kolaboratif. Dengan demikian, card-based game dapat menjadi alternatif strategi pembelajaran aktif yang mendukung pembelajaran matematika di perguruan tinggi.